خصوصية إجراءات البحث والتحري عن الجرائم الجمركية - أميـنة, قاضي (Revue jurisprudence, 2019)
Contrary to what is stated in the procedural criminal law, research and investigation of the customs crimes is characterized by special procedures. The Investigation phase is considered as the first and the most important stage in the course of controlling the customs crime.This is evident from the expansion of the Algerian legislator of persons charged with the inspection of these crimes ، and giving them effective authorities for the purpose of reducing this kind of crimes.The Algerian customs law also includes spcial procedures for conducting the necessary customs investigations notably the procedures of seizure and detection in addition to the procedures established under the general rules ، which gives the procedures of inspection and investigation of the customs crimes the nature of duplication as it s distributed between the customs law and the general procedural criminal law.